The impact of asymptomatic infections: the Italian municipality of Vo’ as a case study - Crisanti, Andrea (Henry Stewart Talks, 2021)
The unique case study of the Italian municipality of Vo’ and the insights it provided, Asymptomatic vs symptomatic COVID-19 infections and their epidemiological impact, Implications on COVID-19 spread in more densely populated areas such as cities, Recent follow-up studies drown from the data at the municipality of Vo’ shedding light on individual antibody responses to and the impact of individual genetic makeups.